PRESEPSI MASYARAKAT TENTANG TAMBANG BIJI BESI DI NAGARI SUNGAI KUNYIT BARAT KECAMATAN SANGIR BALAI JANGGO KABUPATEN SOLOK SELATAN - Rahmatika, Sri Indah - (Pendidikan Geografi, 2014)
Sangir Balai Janggo subdistrict is teritory very famous by itâs plantation in South Solok and rich by nature resource. Like oil palm plantation, rubber plantation, gold mine, and then seed iron mine.The purpose of result is to get data, to process, to analize and to discuss society perseption about seed iron mine existance in west Sungai Kunyit Village, Sangir Balai Janggo subdistrick look at: 1) healty rate, 2) income rate, 3) and street access has used by society of Sungai Kunyit Village. The research is descritave, to be population in this research is society has activity seed iron mine. The sample of research has taken with Random Sampling, the sample ammount to 77 person. Data colletion use blank questionnaire, the analysis has used descriptive statistics.The result of reseach is 1) Society say that agree with existence seed irin mine effected disease from activity of PT.VUMâs mine and to fell up many ISPA illess. 2) Society say that agree about than income that has accepted and solid for to open sidiline effort to increase knock about need. 3) Society say that street has gone by damaged and travelled distance to be longest so that society jaourney activity have the hands tied and very dusty in consequence of seed iron mine activity in Sungai Kunyit Village.